Digital Based Sustainable Tourism Village Brand as a Village Economic Driver - Farhan, Raihan Muhammad; Sunuantari, Manik (Universitas Prof. Dr. Moestopo (Beragama), 2024)
Rural tourism branding is one of the efforts that can generate a major contribution to Indonesian tourism. The variety of cultures and characteristics of Indonesian villages have opportunities in the development of sustainable tourist destinations. However, various fundamental problems have caused many tourist villages to have not maximized their potential. One of the main problems in developing villages as tourist destinations is the lack of promotional activities and branding for differentiation between villages. This study aims to examine digital rural branding activities in Batu Malang City through digital media platforms to form village economic resilience. This study uses the Pentahelix concept with a case study research method in Batu City, Malang. The results of this study indicate that one of the communities that actively carries out branding activities through digital media is the KIM (Community Information Group). KIM uses TV Desa as a rural tourism village branding platform in collaboration with the government, academics, media, and business people. KIM's partnerships with various stakeholders are able to drive opportunities to improve the village economy. Collaboration between elements has encouraged the development of Micro, Small and Medium Enterprises (UMKM) in Batu Malang City so that they can drive the village economy.